Coexistence of Chronic Heart Failure and Chronic Kidney Disease (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Chronic heart failure (CHF) and chronic kidney disease (CKD) often coexist, presenting a significant challenge in healthcare. This article aims to explore the relationship between CHF and CKD in more detail, including their shared risk factors, pathophysiological mechanisms, impact on each other, and management strategies. By understanding these aspects, healthcare professionals can better manage individuals with both conditions and improve their outcomes.